Pattern of Febrile convulsion in Hospitalized Children. (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Summary: The results of a retrospective study of 171 patients with febrile convulsion seen in the Children's Emergency Ward of the Ogun State University Teaching Hospital, Sagamu, between June, 1986 and June 1990, are presented. The mean age of the patients was 3.1 years and the male to female ratio was 1.28:1. Thirty-eight patients (22.2 percent) had a past history of febrile convulsion, while a positive family history of same was obtained in 21 patients (12.3 percent). The commonnest underlying aetiologic factors were malaria in 129 (75.4 percent) and upper respiratory tract infection in 21 patients (12.3 percent). Traditional concoctions in various forms were administered to 90 patients (52.6 percent). The morbidity and mortality in this study were found to be directly related to the administration of traditional concoctions to the children before hospitalization.